(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
Writing is one of major skill for production of any language. However, it is considered as a difficult skill, particular for English as a Foreign Learners. The EFL learners face multiple challenges and problems in this skill. Keeping same in view, the current study was conducted with the aim to explore and investigate the challenges faced by IRAQI EFL learners in writing skills. Further, this study also planned to obtain suggestions from students on how to develop IRAQI EFL learners writing skill. So, focus groups of IRAQI EFL learners were interviewed. Writing sample was collected from 15 EFL learners and scrutiny of sample were conducted in light of thematic analysis techniques. The findings of interviews and analysis of writing sample revealed that main challenges in IRAQI EFL learners are due to insufficient linguistics proficiency, lack of command over grammar, semantic, syntax, vocabulary, lack of ideas and writing anxiety. These challenges are due to various factors including, standard of teaching, traditional teaching methodology, memory based examination system, less motivation, lack of interest in reading and writing. This study also provided short and long term remedial measures for the development of writing skills among IRAQI EFL learners.